Integrating nature-based and outdoor learning through interactive e-books to enhance english skills and physical engagement in students - Melda Veby Ristella Munthe; Vita Riahni Saragih; Anita Sitanggang; Eva Pratiwi Pane; Jaya Tata Hardinata; Minar Trisnawati Tobing; Hery Reynaldi Tarigan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Nature-based and outdoor learning approaches have shown promising results in enhancing English language skills and student engagement. These methods allow students to explore and interact directly with their environment. Interactive e-books have shown promise in enhancing English language skills across various educational levels.  Objective: The research aims to determine the effectiveness of interactive e-books integrating nature-based and outdoor learning to improve students’ English skills and physical engagement. Methodology: This is descriptive quantitative research. The data collection techniques are interviews, questionnaires, and tests. Results: Based on the analysis, the integrated interactive e-book based on nature-based learning and local wisdom is valid and can be used in the learning process. The average value for each aspect is 4.2, which indicates that the e-book is valid.  Discussion: The results of hypothesis testing and gain scores show that students in the experimental class who learned using the integrated interactive e-book based on nature-based learning and local wisdom experienced a more significant increase in learning outcomes than students in the control class. The average student score in the experimental class was 70%, a high category, while the average student score in the control class was 50%, a medium category.